2019
DOI: 10.1186/s12864-019-5670-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling and pathway analysis reveal differences in pituitary gland function, morphology, and vascularization in chickens genetically selected for high or low body weight

Abstract: Background Though intensive genetic selection has led to extraordinary advances in growth rate and feed efficiency in production of meat-type chickens, endocrine processes controlling these traits are still poorly understood. The anterior pituitary gland is a central component of the neuroendocrine system and plays a key role in regulating important physiological processes that directly impact broiler production efficiency, though how differences in pituitary gland function contribute to various g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 78 publications
0
8
0
2
Order By: Relevance
“…However, this increase was accompanied by either no change or inconsistent changes in liver IGF1, IGF2, and IGFR1 or a decrease in IGF1 and IGFR1 in breast muscle, suggesting that IGF1, IGF2, and IGFR1 production are not dependent on GH during late embryonic development. It has been suggested that the somatotropic axis is not fully established until after hatch (Ellestad et al, 2011;Ellestad et al, 2019), and this study provides further evidence that IGF production is likely not GH-dependent in the embryonic somatotropic axis.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…However, this increase was accompanied by either no change or inconsistent changes in liver IGF1, IGF2, and IGFR1 or a decrease in IGF1 and IGFR1 in breast muscle, suggesting that IGF1, IGF2, and IGFR1 production are not dependent on GH during late embryonic development. It has been suggested that the somatotropic axis is not fully established until after hatch (Ellestad et al, 2011;Ellestad et al, 2019), and this study provides further evidence that IGF production is likely not GH-dependent in the embryonic somatotropic axis.…”
Section: Discussionmentioning
confidence: 51%
“…This project was supported by funding from the College of Agricultural and Environmental Sciences, University of Georgia and Agriculture and Food Research Initiative Competitive Grants #2017-67015-26490 (TP andLE) and#2021-67034-35185 (LV andLE) from the USDA National Institute of Food and Agriculture.…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…Ekstrak hipofisa ayam broiler selama ini diketahui mengandung hormon gonadotropin. Penelitian terbaru yang mengevaluasi ekspresi gen global dari ekstrak kelenjar hipofisis anterior ayam Gallus gallus melaporkan terdapat empat hormon hipofisis anterior yang terkandung dalam rangkaian gen yang diekspresikan berbeda-beda yaitu Thyroid Stimulating Hormone, Luteinizing Hormone, Follicle Stimulating Hormone, dan Growth Hormone (Ellestad et al, 2019).…”
Section: Respon Ovulasi Dan Waktu Latensiunclassified
“…In the chicken pituitary, the mRNA expression levels of growth hormone ( GH ) and prolactin ( PRL ) started to increase on embryonic day 16 ( E16 ) and E18, respectively ( Kansaku et al., 1994 ), while those of duck GH and IGF1 started to increase on E25 and E21, respectively ( Hu et al., 2015 ). Although the chicken pituitary transcriptome changes in the post-hatching development have been previously investigated ( Pritchett et al., 2017 ; Ellestad et al., 2019 ), there are still lack of studies on the avian pituitary developmental dynamics during the critical embryo-to-hatchling transition, especially in waterfowls.…”
Section: Introductionmentioning
confidence: 99%